Assessment of the influence of hydrological, environmental, economic, and social indicators on the estimation of a hydrological system's vulnerability to climate change - Ruiz Chávez, Felipe de Jesús; Martínez Bárcenas, Adrián; Gutiérrez Pérez, Joanna Alicia; Orozco Medina, Ismael (Acta Universitaria, 2025)
Evaluating the vulnerability of hydrological systems is essential for designing mitigation strategies against climate change; however, its quantification is complex due to the many variables involved. Environmental, economic, social, and water-related indicators are used to assist in its calculation. Due to its widespread use, a sensitivity analysis has been conducted in this study to assess the influence of 17 indicators on the quantification of vulnerability. To do this, the MPDV1.0 model was used, which allows for calculating environmental, economic, social, and water vulnerability to climate change. Results indicate that six indicators directly influence the variability of vulnerability, underlining the degree of watershed exploitation and aquifer exploitation.